EFEKTIFITAS INISIASI BLADDER TRAINING TERHADAP INKONTINENSIA URIEN PADA PASIEN STROKE NON HEMORAGIK YANG TERPASANG KATETER DI RUANG NEUROLOGI RSUD RADEN MATTAHER JAMBI - Engla Ampia Lestari; Rino M (Universitas Baiturrahim, 2017)
Background : Bladder training is one of the efforts to control bladder function is impaired to normal or optimal function that aims to train neurogenic bladder and restore normal pattern of urination by inhibiting or stimulating spending urine . Method : This study aims to determine urinary incontinence in patients with non- hemorrhagic stroke were catheterized in neurology hospital room Raden Mattaher Jambi The population in this study non- hemorrhagic stroke patients were catheterized as many as 209 people , with a sample of 20 people pre -test and post -test method uses pre - experiment with bentukone - group pretest - posttest design stastistick test used was T Dependent sample taken with technique